2011
DOI: 10.3892/mmr.2011.599
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin�A ameliorates the cytokine secretion profile of lipopolysaccharide-stimulated macrophages by a PPARγ-dependent pathway

Abstract: Abstract. The role of peroxisome proliferator-activated receptors (PPARs) as anti-inflammatory mediators has been established, and the fact that some isoflavones are dual agonists of PPARα/γ indicates the involvement of PPARα and/or PPARγ in the anti-inflammatory action of certain isoflavones. However, the dependency of isoflavones on PPARs in their anti-inflammatory action has not been demonstrated. Here, we report the dependency of an isoflavone biochanin A and the independency of another isoflavone genistei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Isoflavones like biochanin A and formononetin are reported to be potent agonists of PPARα (12,15,16). To determine the effects of red clover extract treatment on certain target genes of PPARα in the liver, we analyzed hepatic ACO, CPT-1, APOC3 and APOA5 mRNA expression in db/db diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoflavones like biochanin A and formononetin are reported to be potent agonists of PPARα (12,15,16). To determine the effects of red clover extract treatment on certain target genes of PPARα in the liver, we analyzed hepatic ACO, CPT-1, APOC3 and APOA5 mRNA expression in db/db diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies have demonstrated that biochanin A, formononetin and genistein, three of the isoflavones from red clover are effective PPARγ agonists (12,15,16). In this study, we demonstrated that red clover extract treatment resulted in activation of known PPARγ-regulated genes in the liver in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that biochanin A improved epithelial barrier function in CaCo-2 cells via inhibition of NF-κB phosphorylation [17]. Biochanin A was found to inhibit LPS-induced TNF-α and IL-6 production in macrophages [18]. Biochanin A also showed anti-proliferative and antiinflammatory activities through inhibition of NF-κB nuclear translocation [19].…”
Section: Introductionmentioning
confidence: 95%
“…It has been shown that biochanin A exhibited broad spectrum anti-inflammatory effects [25]. Biochanin A was found to inhibit TNF-α and IL-6 production in LPS-stimulated macrophages [30]. Studies showed that biochanin A protected dopaminergic neurons against LPS-induced damage through inhibition of pro-inflammatory cytokine production [4].…”
Section: Introductionmentioning
confidence: 98%